IMPACT OF REWARD AND RECOGNITION ON RETENTION OF ACADEMIC PROFESSIONALS IN DEEMED-TO BE UNIVERSITIES OF BENGALURU - Rathi, R.A.; S, Usha (International Journal of Psychosocial Rehabilitation, 2020)
Higher education institutions are on the verge of losing well qualified, experienced, dedicated and skilled academic professionals to well paid offers from the competitors. The attraction and retention of skilled academic professionals has been one of the serious issues in human capital management. In the developing country like India where the number of higher education institution is increasing it is required to have a qualified and skilled academic staff to increase the number of enrollments but higher education institutions have to catch and withhold the qualified professionals. The competition to retain the staff is more in private and Deemed to be universities so the present study is an attempt to study the impact of rewards and recognition on retention of academic professionals. For the purpose of research a survey with questionnaire was used to collect the responses and the hypothesis was analysed using ANOVA which concluded that there is significant impact of reward and recognition on retention of academic professionals.